1989
DOI: 10.1021/la00085a030
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanical behavior of surface monolayers using orthogonal Wilhelmy plates

Abstract: We have studied the stress-strain behavior of three types of carboxylic acid monolayers on the surface of water using orthogonal Wilhelmy plate measurements. Whether a monolayer supports shear (i.e., whether it is a solid) can be determined from these measurements, which were made with commonly available apparatus used forisotherm determination. We found that pentadecanoic acid monolayers do not support measurable shear at any pressure, while octadecanoic and tetracosanoic acid monolayers support shear at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The axis of the hydrocarbon chains in the backfolding lamellae of the 3D crystallites presumably points into the normal direction of the subphase and the negative slope of the surface–pressure area curve might indicate the consecutive swivel‐out/buckling of the rather stiff 2D backfolding lamellae into the third dimension. The surface area per PCL chain segment (not per monomer unit) to be expected in case of a 3D backfolding and a roughly parallel orientation of the subphase normal direction and the chain segment direction in the 3D crystal can be best approximated by the value observed for densely packed alkyl chains and amounts to MMA = 18.6 Å 2 . Comparing this value with the observed value of the mean area per repeating unit above the threshold surface pressure of the 2D‐ to 3D‐transition in a 100% 3D‐film would yield the number of monomer units in the lamellar segment of the backfolding structure.…”
Section: Resultsmentioning
confidence: 85%
“…The axis of the hydrocarbon chains in the backfolding lamellae of the 3D crystallites presumably points into the normal direction of the subphase and the negative slope of the surface–pressure area curve might indicate the consecutive swivel‐out/buckling of the rather stiff 2D backfolding lamellae into the third dimension. The surface area per PCL chain segment (not per monomer unit) to be expected in case of a 3D backfolding and a roughly parallel orientation of the subphase normal direction and the chain segment direction in the 3D crystal can be best approximated by the value observed for densely packed alkyl chains and amounts to MMA = 18.6 Å 2 . Comparing this value with the observed value of the mean area per repeating unit above the threshold surface pressure of the 2D‐ to 3D‐transition in a 100% 3D‐film would yield the number of monomer units in the lamellar segment of the backfolding structure.…”
Section: Resultsmentioning
confidence: 85%
“…It has been shown that the measured isotherms depend on the surface coverage, but can not be readily rescaled by the area per molecule, as it would happen for a simple surface-tension measurement 28 . Furthermore, because of the presence of shear elasticity, by orientating the Wilhelmy probe with different directions compared to the compression axis, it is possible to distinguish shear from dilatational effects 27,30 . Nevertheless, obtaining a high degree of accuracy of the orientation of the Wilhelmy plate is non trivial.…”
Section: Introductionmentioning
confidence: 99%
“…7 The validity of surface pressure isotherms obtained by the continuous compression has previously been questioned by the detailed analysis of glancing angle x-ray measurements of fatty acid Langmuir monolayers which essentially revealed the dependence of the structure of monolayer phases on whether the compression is under an equilibrium condition. [8][9][10] Effects from Wilhelmy plate orientation for monolayers of fatty acids with different chain lengths were discussed by Halperin et al, 11 but overall the problem of pressure measurements with the Wilhelmy method is currently mostly ignored, probably because the technique is so well established. However, addressing such experimental difficulties has become increasingly more important, since in recent years the LB technology has been extended to a number of nonamphiphilic compounds, such as preformed polymers and other macromolecular substances.…”
Section: Introductionmentioning
confidence: 99%